Acute Myeloid Leukemia With CEBPA Mutations: Current Progress and Future Directions - Su, Long; Shi, Yuan-Yuan; Liu, Zeng-Yan; Gao, Su-Jun (Frontiers in Oncology, 2022)
Mutations in CCAAT enhancer binding protein A gene (CEBPA) are one of the common genetic alterations in acute myeloid leukemia (AML). Recently, emergence of new evidences makes it necessary to reconsider the subsets and treatment of AML patients with CEBPA mutations. This review will summarize the history of research progress of CEBPA mutations in AML, the heterogeneities of AML with CEBPA double mutations (CEBPAdm), and two special subtypes of CEBPA mutated AML. We will discuss the treatment of AML with CEBPA mutations as well, and finally propose a new algorithm for the treatment of these patients, including both familial and sporadic CEBPA mutated AML patients. This review may be beneficial for further investigation and optimizing clinical management of CEBPA mutated AML patients.